Relationship With Prewedding Sex Behavior In Adolescents Of High Schools In Bulukumba District - Fatmawati; Irfanita Nurhidayah; Nila Arfila (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
Premarital sexual behavior in adolescents has increased from year to year which has an impact on the quality of adolescents, at risk of contracting HIV / AIDS, early marriage, unwanted pregnancy, and continued abortion. Teenage knowledge about the dangers of premarital sexual behavior is very little. The family still considers taboo everything related to sex and counseling from the government or the school is still lacking. While adolescent relationships are now increasingly difficult to control. This study aims to determine the relationship of promiscuity with premarital sexual behavior in high school adolescents in 2018. The design of this study uses analytic observational research with a cross-sectional approach. The population in this study was all 118 high school students with a random sampling technique with a systematic random sampling approach to modification of simple random sampling. The number of samples in this study was 55 people. Data obtained through questionnaires made by researchers to respondents who have tested the validity. Data analysis used the Chi-square test with significance level α = 0.05. The results of the data analysis show that p = 0.00 means that there is a relationship between promiscuity and premarital sex behavior among high school adolescents in Bulukumba in 2018. From the results of this research, suggestions that can be given to related institutions, in this case, the Health Office and high school schools can increase counseling about premarital sexual behavior in adolescents at an early stage and need to limit relationships between adolescent boys and girls.